New World Soundings Culture and Ideology in the Americas - Morse, Richard M. (Johns Hopkins University Press, 1989)
In this book, cultural historian Richard Morse takes a series of sharply focused looks at the Americas. He inquires into the ways in which speech and poetry evoke the common historical experience of North and South America and examines the transatlantic "sea changes" of European languages. He uses political ideology to contrast the traditions of Anglo and Latin America, while surveying contemporary pressures for ideological change. In the book's final sections, he addresses the North-South transaction from yet three more angles, ruminating on the problems involved in conveying the Latin American experience to U.S. students, considering the impediments to U.S.-Puerto Rican understanding, and recounting the mythic adventures of McLuhanaima, "the world's first Brazilianist," as he travels through the exotic land he has chosen for definitive research.